The design of furnace for biochar production by using vacuum pump and temperature manual control. Issue 1 (January 2021) - Nurhidayah, N; Peslinof, M; Afrianto, M F; Fahyuan, H D; Heriansyah, H; Damris, M
Abstract: Temperature control is very prominent to be done in producing biochar, because the quality of biochar depends on combustion temperature and the amount of oxygen existing when the combustion process is happening. In this research, the designing of furnace for biochar production by using vacuum pump and temperature manual control had been done. The fuel used was LPG gas. The furnace was designed by having two parts which are cylinder tube for biochar production and tube feet as the holder of the kiln. The calibration of the furnace for biochar production was done to find out the temperature and the pressure that can be generated and its effect toward produced biochar. The calibration was done by using vacuum pump to vacuum the combustion chamber and temperature manual control as temperature indicator. There were two steps for this furnace calibration, first, the leakage test and second, combustion test of biochar production. The leakage test was done by using bubble test method. The result showed that there were still some leakages happened, but they were fixed with glue on the leak parts. As the final result of the leakage calibration, the vacuum condition obtained was -25 cmHg. And as the result of biochar combustion as long as one and two hour, the temperature reached 280 0 C and 250 0 C.